Pengaruh Motivasi, Disiplin Kerja, Penempatan dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada BPR Tawangmangu Jaya - Anti, Mita Ardi, Drs. Wiyadi, M.M., Ph.D (2016)
This research aimed at examining the influences of motivation, work discipline, placement and work environment collectively on the job satisfaction of employees at BPR Tawangmangu Jaya. This reserach was conducted at BPR Tawangmangu Jaya using sample as many as 46 respondents taken through the technique of saturated sample. The technique of data collection used questionnair, meanwhile, the technique of data analysis uses multiple linear regression analysis and classical asumption test. Based on the result of multiple linear regression analysis, it was obtained a regression equation: Y = 7.676 + 0.165 X1 + 0.193 X2 + 0.332 X3 + 0.236 X4 + e. It meant that the variables of motivation, work discipline, placement and work environment had a positive influence on the job satisfaction. If motivation, work discipline, placement and work environment are increased, the job satisfaction will follow to increase. The influence test conducted individually showed that the placement and work environment individually had positive and significant influence on the job satisfaction. It was proved from the result of t test in which tcount>ttable. The influence test conducted collectively showed that the variables of motivation, work discipline, placement and work environment had been fit as the predictors of job satisfaction of the employees. It was proved from the result of F test in which Fcount>Ftable. To increase the job satisfaction of the employees, the management of BPR Tawangmangu Jaya was hoped to always manage the available Human Resources carefully and pay attention to the policy of placement and work environment, and the employees of BPR Tawangmangu Jaya was hoped to have a high loyalty to the company, therefore, the existing policies were not considered as burdens because they were important factors in increasing the job satisfaction of employees.